Finance and Development, June 1970. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1970)
This paper explains how the World Bank carries out its most characteristic activity: the identification, preparation, appraisal, and supervision of projects for economic development. The paper highlights that project lending is intended to ensure that the World Bank funds are invested in sound, productive projects with the purpose of contributing both to the borrowing country's capacity to repay and to the development of its economy. It is in the coincidence of these two purposes that the Bank's functions as an international financial institution merge with those that it has increasingly assumed as a development institution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet